THE INFLUENCE OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT CV MORA SENTOSA EAST JAKARTA - Astuti, Febri Widya; Indrajaya, Titus; Nurminingsih; Kwarnanto (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Effective employee performance plays a pivotal role in an organization's success, directly shaping overall productivity and efficiency. This study delves into the connection between compensation, work environment, and employee performance within CV Mora Sentosa, located in East Jakarta. Quantitative research involving a sample of 40 participants was conducted. The findings highlight a significant and positive correlation between compensation and the work environment (T-Statistic = 81.909, p < 0.05). It is worth noting that while compensation alone does not exert a significant impact on employee performance (T-Statistic = 0.108, p > 0.05), a positive work environment does indeed wield a remarkable influence on employee performance (T-Statistic = 8.685, p < 0.05). This research underscores the pivotal role of cultivating a positive work environment to bolster employee performance. Such insights can serve as a guiding light for organizations aiming to deploy strategies that optimize both compensation and work environment variables. By doing so, organizations stand to enhance overall employee performance, thus fostering a path to greater organizational triumph.